1970
DOI: 10.1073/pnas.66.3.1008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of a Membrane-Bound D-(-)-Lactic Dehydrogenase to Amino Acid Transport in Isolated Bacterial Membrane Preparations

Abstract: Abstract. The conversion of D-lactate to pyruvate in isolated membrane preparations of E. coli ML 308-225 markedly stimulates the transport of proline, glutamic acid, aspartic acid, asparagine, tryptophan, lysine, serine, alanine, and glycine. The uptake of histidine, phenylalanine, tyrosine, leucine, isoleucine, and valine by the membranes is also markedly stimulated by this conversion, although these amino acids are taken up much less effectively than those mentioned previously. The uptake of arginine, methi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 11 publications
3
39
0
Order By: Relevance
“…As for the synergism of ribosides with amino acids as germinants for Bacillus spores, Gould and Sale [6], from their study on the germinant action of hydrostatic pressure, have suggested that both riboside and pressure may function to increase the spore permeability to exogenous or endgenous a-amino acids. In this connection, Kaback and Milner [8] recently …”
mentioning
confidence: 99%
“…As for the synergism of ribosides with amino acids as germinants for Bacillus spores, Gould and Sale [6], from their study on the germinant action of hydrostatic pressure, have suggested that both riboside and pressure may function to increase the spore permeability to exogenous or endgenous a-amino acids. In this connection, Kaback and Milner [8] recently …”
mentioning
confidence: 99%
“…Membrane vesicles from E. coli ML308-225 convert accumulated methionine to an unknown compound (Kaback & Milner, 1970), which may be either the corresponding a-keto acid or possibly methionine sulphoxide formed in the presence of ascorbate-PMS. In Ps.…”
Section: Discussionmentioning
confidence: 99%
“…Kay & Gronlund (1969a, b) found that, although Pseudomonas aeruginosa transports methionine, the amino acid is a source of nitrogen only. Kaback & Milner (1970) reported that methionine is converted to an unidentified metabolite by the isolated membranes from E. coli ~~3 0 8 -2 2 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering studies of Kaback with isolated cytoplasmic membrane vesicles unequivocally demonstrated that ATP nor any other phosphorylated intermediate functioned as the direct energy source for facilitated solute transport (Kaback and Milner, 1970). These observations were initially explained by Kaback and co-workers with a model in which the carrier protein was depicted as an electron transfer chain intermediate (Kaback and Barnes, 1971).…”
Section: Introductionmentioning
confidence: 97%